PENGETAHUAN DAN PELAKSANAAN INISIASI MENYUSU DINI OLEH BIDAN PRAKTIK SWASTA DI KECAMATAN GAMPING - Lia Dewi, Vivian Nani (Jurnal Media Ilmu Kesehatan, 2012)
Background: The vision of Making Pregnancy Safer (MPS) is safe pregnancy and childbirth in Indonesia, and babies are born alive and healthy. Early Initiation of Breastfeeding (EIB) is one of the interventions to reduce infant morbidity and mortality. Objective:To observe the knowledge and behavior of privately practicing midwives on early initiation of breastfeeding in Gamping, Yogyakarta. Methods: This was a descriptive study using qualitative and quantitative methods with a casestudy design. The subjects were privately practicing midwives located in Gamping Sub-district,Yogyakarta. Results: In terms of knowledge, privately practicing midwives in Gamping Sub-district had already had good knowledge about early initiation of breastfeeding and in terms of behavior as the result of observations and interviews a privately practicing midwives performing deliverycare had applied early initiation of breastfeeding to each baby born. Conclusion: Privately practicing midwives in Gamping Sub-district had already had good knowledge about EIB and had carried out it correctly. Keywords: Privately practicing midwives, early initiation of breastfeeding